2006
DOI: 10.1346/ccmn.2006.0540108
|View full text |Cite
|
Sign up to set email alerts
|

Baseline studies of the clay minerals society source clays: Specific surface area by the Brunauer Emmett Teller (BET) method

Abstract: Specific surface area measurements of The Clay Minerals Society source clays were made by the Brunauer, Emmett and Teller (BET) method of adsorption of nitrogen gas. Two replicate measurements of specific surface area were performed for each source clay. All pair values were within 3%, which is very good agreement for this type of measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(91 citation statements)
references
References 60 publications
8
82
1
Order By: Relevance
“…Non-polar molecules, such as nitrogen, are known to only adsorb to the external surfaces of montmorillonite and thus provide a direct measurement of the external surface area including clay microstructure (Hendricks et al, 1940;Mooney et al, 1952;Pennell et al, 1992). The BET surface area for SWy-2 is 318.2(±2.2) cm 2 /mg (Dogan et al, 2006), as reported by the Clay Mineral Society and independently confirmed by the authors by BET analysis using a volumetric expansion technique with nitrogen as the adsorbate. The calculated BET surface area was within the uncertainty reported by the Clay Mineral Society.…”
Section: Clay Surface Areasupporting
confidence: 57%
“…Non-polar molecules, such as nitrogen, are known to only adsorb to the external surfaces of montmorillonite and thus provide a direct measurement of the external surface area including clay microstructure (Hendricks et al, 1940;Mooney et al, 1952;Pennell et al, 1992). The BET surface area for SWy-2 is 318.2(±2.2) cm 2 /mg (Dogan et al, 2006), as reported by the Clay Mineral Society and independently confirmed by the authors by BET analysis using a volumetric expansion technique with nitrogen as the adsorbate. The calculated BET surface area was within the uncertainty reported by the Clay Mineral Society.…”
Section: Clay Surface Areasupporting
confidence: 57%
“…It was used without further purification. Its CEC value was 123 ± 3 mmol/100 g (Borden and Giese 2001) as determined by the ammonium acetate method, its layer charge being 0.32 equiv/mol per (Si,Al) 4 O 10 unit (Mermut and Lagaly 2001) and its external surface area being 65 m 2 /g (Dogan et al 2006). The MB used (CAS #7720-79-3) was purchased from Sigma-Aldrich (St. Louis, MO, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…6 Surface areas of clays are typically measured by the BET method, 7 in which the adsorption isotherms are found by exposing the clays to inert gases. [8][9][10] In a study of the microporosity of montmorillonites, D.W. Rutherford et al 11 concluded that the interlayer space of montmorillonites exchanged with small metal cations (such as Na + ), is too narrow to be accessible even to small nonpolar gases (like N2).…”
Section: Introductionmentioning
confidence: 99%